2002
DOI: 10.1002/cncr.10586
|View full text |Cite
|
Sign up to set email alerts
|

A problem‐solving approach to stress reduction among younger women with breast carcinoma

Abstract: BACKGROUND Previous research indicates that younger women (i.e., ≤ 50) with breast carcinoma experience greater emotional distress than older women (i.e., > 50) and that coping style is significantly related to the psychosocial adjustment of women with this disease. The purpose of this study was to evaluate through a randomized controlled trial the effectiveness of a problem‐solving training intervention designed to empower women with breast carcinoma to cope with a range of difficulties when diagnosed in mid‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(98 citation statements)
references
References 70 publications
3
92
2
Order By: Relevance
“…32 Studies have described interventions combining face-to-face with telephone contact with positive outcomes. [33][34][35] For instance, in the UK an RCT with over 300 patients found that a very brief cognitive behavioural therapy (CBT) intervention promoted earlier adjustment to illness among patients at high risk of developing affective disorders. 35 …”
Section: Telephone Counsellingmentioning
confidence: 99%
“…32 Studies have described interventions combining face-to-face with telephone contact with positive outcomes. [33][34][35] For instance, in the UK an RCT with over 300 patients found that a very brief cognitive behavioural therapy (CBT) intervention promoted earlier adjustment to illness among patients at high risk of developing affective disorders. 35 …”
Section: Telephone Counsellingmentioning
confidence: 99%
“…However, the benefits of the intervention over standard care did not reach statistical significance for regimens within the moderate/high or low emetogenic groups. The evidence was inconclusive regarding which patients have the most unmet needs, 10,11 or whether screening for unmet needs may improve patient-reported outcomes. 13,30 The findings of the current study support that telephone-based nursing care is appropriate and acceptable, [10][11][12]15 yet the optimal dose intensity or timing for all patients remain elusive.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence was inconclusive regarding which patients have the most unmet needs, 10,11 or whether screening for unmet needs may improve patient-reported outcomes. 13,30 The findings of the current study support that telephone-based nursing care is appropriate and acceptable, [10][11][12]15 yet the optimal dose intensity or timing for all patients remain elusive. 31 Although the current intervention did not affect patient-reported outcomes, the entire sample demonstrated patterns of change, which can inform future work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…45 Eligible patients were recruited from a network of sites in Rhode Island, southeastern Massachusetts, Philadelphia, and Newark, New Jersey, between April 1996 and November 1999. Study eligibility criteria included women aged 50 or younger who had no prior history of breast cancer, who had a tissueconfirmed diagnosis of stage I to IIIA tumors, and who were initiating their first course of chemotherapy treatment.…”
Section: Samplementioning
confidence: 99%